Studies on Ulama’s Flow in The Modern Era from an Islamic Perspective - Mala Komalasari; Rantika Dwi Maharani; Ahmat Nurulloh (Dirasah International Journal of Islamic Studies, 2023)
In the social life of the community, there must be norms that apply as a form of firmness in obeying the rules, so that it creates a sense of security for community members in the social life of the community. These norms are noble values that serve as benchmarks for social behavior. If the behavior that exists in the community is in accordance with the prevailing norms, then the behavior will be well received by the community. And if it applies otherwise, then the behavior is not accepted by the community, because it is deemed to deviate from the prevailing norms, but in fact, even though the times have evolved in this modern era, the existence of local beliefs such as belief in dynamism and animism is still developing. In the life of religious communities, such deviations are often seen in the form of deviant behavior of diversity. Moreover, there is an occult flow that is still developing in modern society. If it continues into the future, then it can change the thinking patterns of modern society into those who are still primitive Kejawen. So that this can lead to deviations from an Islamic perspective.